Impact of abdominal aortic aneurysm screening on quality of life. Issue 3 (5th February 2018) - Bath, M. F.; Sidloff, D.; Saratzis, A.; Bown, M. J.; ,
Abstract : Background: Screening for abdominal aortic aneurysm (AAA) is known to reduce AAA‐related mortality; however, the psychological impact of population AAA screening is unclear. The aim was to assess the impact of AAA diagnosis on quality of life (QoL) using data from an established AAA screening programme. Methods: Mental and physical QoL scores for men diagnosed with AAA through participation in the English and Welsh AAA screening programmes were compared with no‐AAA controls. Participants were identified through the United Kingdom Aneurysm Growth Study (UKAGS), a nationwide prospective cohort study of men with an AAA of less than 55 mm diagnosed through voluntary participation in screening. The UKAGS participants completed QoL questionnaires at the time of screening and annually thereafter. Results: A transient reduction in mental QoL scores was observed following the diagnosis of AAA, returning to baseline levels after 12 months. Physical QoL remained consistently lower in the AAA cohort. Participants thought about their AAA and the AAA growth progressively less 12 months after the initial screening diagnosis. AAA growth rate had no influence over QoL parameters. Discussion: This study suggests that screening for AAA does reduce mental QoL; however, this effect is transient (less than 12 months). Men diagnosed with AAA have a consistently worse physical QoL compared with controls. Abstract : Small initial reduction